A Set of International OECD and ICGN Corporate Governance Standards After Financial Crisis, Corporate Scandals and Manipulation - Applications for Nigeria and Implications for Developing Countries - Huy Dinh Tran Ngoc; Thuy Nguyen Thi; Phuong Le Thi My; Dat Pham Minh; Dung Vu Trung; Manh Pham Tien (Management, 2020)
A statement by ACCA in May 2009 that any corporate governance system should consider factors such as transparency, accountability, fairness and responsibility, raises issues in this field over past few years. There are also a few researches which have been done in the field of international corporate governance standards. This paper chooses a different analytical approach and among its aims is to give some certain systematic conclusions.